Development of Teaching Devices Based on Ethnomathematics and RME to Enhance Mathematical Literacy: Bibliometric - Salman Hanafi; Sarwi Sarwi; Onwardono Rit Riyanto (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to examine the development of teaching materials based on ethnomathematics and Realistic Mathematics Education (RME) to enhance students' mathematical literacy. The research employs the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), encompassing the stages of identification, screening, eligibility, and inclusion of relevant literature. The literature review focuses on studies related to the integration of local culture into mathematics instruction through an ethnomathematics approach and the application of RME as a pedagogical strategy. The findings indicate that teaching materials incorporating ethnomathematics and RME are effective in improving students' conceptual understanding, critical thinking skills, and mathematical literacy. This study provides recommendations for curriculum developers and educators to integrate local cultural values into contextual and relevant mathematics learning.